Future Challenges in Medical Education - Mohamed, Abdul Latiff (Bangladesh Journal of Medical Science, 2010)
There have been many models proposed in the past decade on the best practices in teaching and learning processes, especially in medical education. The main trend is a major shift from tutor-centered system to student-centered learning processes with the aid of information technology and communications, more often called e-learning. The introduction of problem-based learning (PBL) and student centered team based learning SCTL) in the early 80's became a trend which spread like wildfire in most modern medical schools. The acceptance of these new methodology received different reactions, mainly from the tutors, most of whom were split on whether the need of change was really necessary, asking the main question of "what is wrong with the traditional methods" or "have we produced inefficient doctors through the years of traditional system teachings". It seemed for some time that a significant number of older generation tutors were much more comfortable with the methods they were used to. Considerable curricular changes were made by many medical institutes to implement the student centered learning system. This approach, however, necessitated the training of tutors and the creation of a learning environment, which was later found not to be too easy. The major consideration of a shift in techniques of teaching learning processes is the understanding of the trends in the younger generation of the Y2K century. A generation which prefers to express rather than listen, to research and find rather than being spoon-fed and a generation where knowledge is always available whenever they are connected to the internet. Hence the change of the role of tutors to be facilitators rather than content providers was seen to be more acceptable to the new generation of students. The advancing information technology (IT) has been able to provide the necessary tools to achieve that objective. The students may be granted the opportunity to have more freedom in selecting their learning material and to enjoy a degree of distance-learning. The consequence of applying IT in medical institutes would, probably, enforce the trend towards moving to a student-centered learning environment, inducing hesitant tutors to become more compliant with the change. The future medical curriculum is anticipated to be more student-centered, more modular, more integrated, more PBL or SCTL-oriented and more inter-institutionalized, with less memorizing and with more learning about learning. In addition, medical education as a whole at least in part, would be, performed at distance. The future medical tutor may have to be more PBL-oriented, more qualified in learning strategies, competent in small group (probably single-student) learning, more of a 'mentor' or a 'facilitator' than of a 'teacher', able to train students at higher cognitive levels rather than being an 'authority' in its field. He has no choice but to be fluent in IT, and interactive with learning via other learning-collaborating institutions. Key Words: Medical education. DOI:10.3329/bjms.v9i1.5226 Bangladesh Journal of Medical Science Vol.09 No.1 Jan 2010 4-13